OPTIMIZATION OF SURFACE ROUGHNESS AND CONE ANGLE IN AWJ MACHINING OF AIRCRAFT MATERIAL USING RSM: Received: 14th October 2021; Revised: 29th December 2021, 11th February 2022, 15th February 2022; Accepted: 17th February 2022 - Deshpande, Yogesh V; Barve, P S; Madankar, T A; Pund, S S (MATTER: International Journal of Science and Technology, 2022)
Abrasive water jet machining (AWJM) of aircraft material is a difficult process using conventional machines. Machined parts of Inconel 718, a nickel-based alloy (aircraft material) are widely used in the aerospace industries. However, these alloys are expensive and difficult to machine. The objective of this article is to optimize AWJM process parameters. Response Surface Methodology (RSM) is planned with travel speed, abrasive flow rate, and stand-off distance as inputs. The response models of surface finish and cone angle show the correlation coefficient `R2` of 96.94% and 96.67%, respectively. 3D surface plot with analysis of variance (ANOVA) is presented to distinguish significant AWJM parameters. The work revealed that travel speed is a significant factor for surface finish and cone angle. Multi-response optimization results in the best optimal values of traverse speed; abrasive flow rate and standoff distance are 200 mm/min, 460 g/min, and 4 mm respectively. This research outcome showed more than 90 % of accuracy for both the responses. This article is helpful to the AWJM centers to select optimal machining parameters for achieving the desirability in the machining of Inconel 718. The obtained novel results confirmed that such a technique can be implemented to identify optimal parameters in the machining of different materials.